Reproductive biology of mackerel scad (Decapterus macarellus Cuvier, 1833) in The North Halmahera waters - Restiangsih, Yoke Hany; Fauzi, Moh; Taufik, Muhammad; Kembaren, Duranta D; Lestari, Pratiwi; Yahya, Muhammad Fadli; Nuratmojo, Nuratmojo (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
Studying the biological reproduction of fish is important for determining the spawning season and providing several management options to protect the fisheries. The study conducted length and biology reproduction sampling of Mackerel scad (Decapterus macarellus) caught by mini purse seine landed in Tobelo coastal fishing port during 20152016. The total sample consisted of 1228 individuals, 526 males and 671 females with size distributions ranging from 12.50 to 29.90 cmFL. Results showed that there were 432 immature and 94 mature male fish and 582 immature and 89 mature female fish. The growth pattern for male fish is negative allometric (b3) while for females is isometric (b=3). The highest GSI value for male was recorded during May and November, while for females it was in May and October. Based on this result, the spawning season of mackerel scad in the North Halmahera waters is predicted to occur in March-May and August-October, by the first and second transition seasons. The study found that the length at first maturity (Lm) was 24.90 cmFL for male fish and 26.41 cmFL for female fish, the Lm bigger than Length at first capture (Lc) of 21.93 cmFL. This means the fish was caught before mature gonads and had a chance to spawn.Keywords:Mackerel scadSmall pelagic fishHalmahera watersGonadosomatic indexSpawning season